Penerapan arsitektur berkelanjutan pada redesain pusat pengolahan karet di Kabupaten Bulukumba - Budhiyatna, Andi; Nursyam, Nursyam; Rahim, Rahmiani (Teknosains, 2024)
Rubber is an important plantation commodity both as a source of income, employment opportunities and foreign exchange, rubber is also a driver of economic growth in new centers in areas around rubber plantations as well as preserving the environment and biological resources. Rubber commodities per year are also decreasing due to poor factory conditions, therefore it is necessary to renovate or redesign buildings in order to increase the amount of production each year. This research aims to realize national standard rubber processing by applying the concept of sustainable architecture as an approach or effort made to minimize environmental problems at the rubber processing center in Bulukumba district. The research method used is descriptive qualitative, collecting primary data by means of field surveys/observations and interviews. Secondary data collection is carried out by collecting literature study data, journals or scientific works related to the title, books, reading materials related to the title, and other literature. By using the concept of sustainable architecture in designing the rubber processing center in Bulukumba district, it is hoped that natural resources and land potential will not be used haphazardly, using land potential for energy efficient architecture and so on.